EFEKTIVITAS MANAJEMEN PENDIDIKAN DALAM PEMBELAJARAN AGAMA ISLAM UNTUK MEMBINA SIKAP DAN PENGAMALAN KEAGAMAAN SISWA DI KELAS V DAN VI SD PLUS AL-ISLAM KECAMATAN WANAYASA KABUPATEN PURWAKARTA - Hamdani, Hilman (STKIP Subang, 2017)
This study was conducted based on the low of religious practice of students which is the implementation of the learning outcomes of religious knowledge obtained anywhere, especially in SD Plus Al-Islam. Therefore, in the implementation of the school should be able to realize the management of education well, because the success of learning is strongly influenced by management effectiveness formulated. Islamic religious material in SD Plus Al-Islam is a distinctive feature that distinguishes it from other elementary schools. Therefore, the school should really be able to streamline the management of education in Islamic learning to improve the quality or quality of education, especially in religious practice. This study, included in qualitative descriptive research. The author collects data using observation, interview, and documentation methods. The results of research on the effectiveness of management education in Islamic learning to foster attitudes and religious practices of students, especially in performing prayers sunnah duha every morning, reading or memorizing Al-Quran, charity, and say hello. The overall management implementation process includes organizing, implementing and valuing systems. While the religious practice of the students is very diverse, in addition to the school management that must be considered, motivation, coaching, supervision of teachers, and environmental factors must also be considered. So the effectiveness of management in SD Plus Al-Islam Wanayasa Purwakarta was effective and can improve the attitude of religious practice of students.